Design of a Monitoring and Nutrient Management System Based on Internet of Things (IoT) for Hydroponic Method Using MIT App Inventor - Priawardana, Shandy Gilang; Surriani, Atikah (Departemen Teknik Elektro dan Informatika Sekolah Vokasi UGM, 2025)
Hydroponics is an agricultural method that uses a growing medium with low nutrient content. In hydroponics, nutrients are required. These nutrients are very important for plant growth in hydroponics. If hydroponic plants lack nutrients, they will die. Water needs in hydroponic reservoirs also need to be considered, so that the water in hydroponics remains stable. Other factors such as water temperature are also important in the hydroponic method. High temperatures can inhibit plant growth and can cause plants to grow faster (bolting). Therefore, the design of temperature monitoring, as well as nutrient management and water level in hydroponic reservoirs based on the Internet of Things (IoT) is made. This tool can manage hydroponic systems efficiently and is easy to operate because it is IoT-based, so that farmers can monitor and manage only via Smartphone on the MIT App Inventor application. This research method has several important stages, namely analysis of the needs of tools and materials, tool design, functional testing of tools, and data analysis. The system will measure the value of nutrients, water temperature, and water level. From this data, it will be processed and arranged for monitoring and management in hydroponic. The results of this final project are the average TDS sensor error of 3.9232%, the average HC-SR04 ultrasonic sensor error of 3.53%, the average DS18B20 temperature sensor error of 2.7513%. This tool can perform monitoring and nutrient management in IoT-integrated hydroponics well, because the resulting error is below 5% and the system runs well.